Increasing Customer Satisfaction With Price Perception Through Customer Decision Mediation During The Covid-19 Pandemic - Sihombing, Rusman Efendi; Parlagutan Silitonga (Jurnal Ekonomi, 2024)
This study aims to determine the role of Customer Decision that mediates the relationship between Price Perception and Customer Satisfaction in a local restaurant chain. Hypothesis testing uses the SEM method with SmartPLS 3.0. The questionnaire was distributed to customers using a purposive sampling technique with a final sample size of 250 respondents. The results of the study indicate that price perception has an effect on customer decision. Customer decision significantly affects customer satisfaction. Price perception significantly affects customer satisfaction both directly and indirectly. This study adds to the understanding of the price perception-customer satisfaction relationship chain that can be expanded by adding customer decision as a mediator of customer satisfaction so that a new chain of price perception-customer decision-customer satisfaction relationships is formed. So it can be suggested to restaurant managers to make improvements in matters related to price perception, customer decision, and customer satisfaction.